Effects of fading channels and interference on Bit-Error Rate (BER) performance of rotated QAM signal - Loh, Yan Wen (Nanyang Technological University, 2022)
The Quadrature Amplitude Modulation (QAM) is a digital modulation scheme that is widely used in the communication system. The rotated QAM is a variation of QAM where the constellation is rotated by an angle about the axis. The focus of this project is to document the performance of the conventional and rotated QAM schemes simulated under various fading channels such as the AWGN, Rayleigh fading and Rician fading. The simulation will be done on MATLAB and the Bit Error Rate (BER) results will be used for comparison between the theoretical and simulated results. The report will begin with the theoretical background various digital modulation scheme and fading channels. Next the simulation results and conclusion on the project.